TATA KELOLA PENDIDIKAN ISLAM YANG TRANSPARAN DAN ADIL: ANALISIS KEBIJAKAN PENDIDIKAN DI AICC VICTORIA - Annisa Sandy Hudha; Safira Mufida ‘Azmi (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze how enrolment and tuition fee policies are implemented at the Australian Islamic Centre College (AICC) in Victoria. The research uses a qualitative method with a library-based approach by examining various official documents, institutional policies, and academic sources related to enrolment agreements, admission policies, and enrolment regulations. The findings show that AICC upholds the principles of transparency and accountability by providing clear information, open enrolment agreements, and a structured monitoring system to protect students’ rights. However, the institution’s financial system still faces challenges, particularly for students from low-income families. Therefore, a more equitable funding model is needed, such as scholarship programs and community support. Overall, AICC’s policy reflects a professional and transparent model of Islamic educational management that seeks to maintain a balance between institutional growth and social justice.